An Extended Review of The Artistic Sphere: The Arts in Neo-Calvinist Perspective - Kresser, Katie (Christian scholar's review, 2024)
The Artistic Sphere: The Arts in Neo--Calvinist Perspective Roger D. Henderson and Marleen Hengelaar--Rookmaaker, eds Published by IVP Academic in 2024 432pp/$ 45.00 / 978-1514007976